2021
DOI: 10.3390/pharmaceutics14010042
|View full text |Cite
|
Sign up to set email alerts
|

“Smart” Polylactic Acid Films with Ceftriaxone Loaded Microchamber Arrays for Personalized Antibiotic Therapy

Abstract: Bacterial infections are a severe medical problem, especially in traumatology, orthopedics, and surgery. The local use of antibiotics-elution materials has made it possible to increase the effectiveness of acute infections treatment. However, the infection prevention problem remains unresolved. Here, we demonstrate the fabrication of polylactic acid (PLA) “smart” films with microchamber arrays. These microchambers contain ceftriaxone as a payload in concentrations ranging from 12 ± 1 μg/cm2 to 38 ± 8 μg/cm2, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
8
0
2
Order By: Relevance
“…The molding of fiber mats was conducted with the alumina target with the ablated pattern of pits with a diameter of 24 μm. The existing systems as microchambers [ 17 , 34 ] inspired the application of the lithography techniques to obtain the fiber micro relief for the higher thickness of the obtained films. The optical image of the modified fiber collector was provided in Figure 4 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molding of fiber mats was conducted with the alumina target with the ablated pattern of pits with a diameter of 24 μm. The existing systems as microchambers [ 17 , 34 ] inspired the application of the lithography techniques to obtain the fiber micro relief for the higher thickness of the obtained films. The optical image of the modified fiber collector was provided in Figure 4 a.…”
Section: Resultsmentioning
confidence: 99%
“…The modification of the fiber collector was conducted with the laser ablation method [ 34 ]. The pattern of pits was engraved in the aluminum plate with the following parameters: laser wavelength 532 nm and 20 pulses per pit, where each pulse is 50 μJ.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the improvement of treatment methods and surgical techniques and the emergence of new highly active antibiotics, the recurrence rate remains high. The use of various systems to deliver antibiotics to the site of infection has become a common method of local suppression that continues to improve [9][10][11][12]. Over the years, several options for silver-based [13] and iodine-based [14] antibacterial coatings have been developed to reduce the risk of postoperative infections after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Microchamber arrays are formed by pressing together flat and embossed hydrophobic polymer films filled with the drug under slight heating (55–80 °C for 5–30 s). Using in vitro and in vivo models, it was proved that such a method of encapsulation allows retention of the biologically active properties of glutamic acid [ 22 ], nerve growth factor (NGF) [ 23 ], α-amylase [ 24 ], doxycycline [ 25 ], ceftriaxone [ 26 ], epinephrine (adrenaline) [ 21 ], and methylprednisolone [ 16 ]. It has also been shown that this biomaterial can release the drug both protractedly [ 16 , 19 ] and quickly (under external influences such as laser radiation [ 14 , 22 , 27 , 28 , 29 ] and high-intensity focused [ 19 ] and therapeutic [ 21 , 26 ] ultrasound).…”
Section: Introductionmentioning
confidence: 99%